Healthcare waste hazards assessment using EWGM-FMEA: Case study in Oman. Issue 1 (31st December 2023) - ALMashaqbeh, Sahar; ALKhamisi, Yousef Nasser
Abstract: In the last years, particularly after Covid-19, Health care waste (HCW) has increased significantly due to the increasing population and number of healthcare organizations. HCW produces a significant risk of infectious contamination and injury. Accordingly, healthcare waste management plays a vital role in creating waste management strategies, and policies and implementing waste management plans. To build robust healthcare management systems, the risk assessment process is a key step. This paper assesses the top hazards of healthcare waste at Sultan Qaboos University Hospital (SQUH) in Oman using the Exponential Weighted Geometric Mean-Failure Mode and Effect Analysis (EWGM-FMEA). Fifteen healthcare waste hazards were selected to apply the tool. These hazards are ranked to prioritize the top hazards wastes. This assessment helps in identifying the most crucial hazards, whiche the policymakers should pay attention thus, the main countermeasures could be conducted. These hazards were proposed based on the conducted survey questionnaire and interviews accordingly, and analyses of the data have been carried out. The applied tool examined the importance of quantifying healthcare waste to apply the appropriate corrective actions which can be applied to mitigate the harm and the negative effects of healthcare waste. The results of the assessment tool will help policymakers in developing clear plans for management, disposal of wastes, and segregation. Furthermore, prioritizing healthcare waste explored the importance of integrating tthe raining plans of workers with the healthcare waste management policy. Although the prospective managerial and policy implications of this research, some limitations could be studied by future researchers. Firstly, the sample covered one hospital that may be representative of only one hospital in Oman which constrains the generalization of results. Secondly, the number of identified waste hazards is fifteen so, increased the number of hazards may help policymakers in building a more effective healthcare waste management plan which will reflect in improving the healthcare management system in the organization, mitigating the harmful effects on human health and the negative effects on the environment.